2019
DOI: 10.1186/s12936-018-2636-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring malaria diagnosis and treatment coverage in population-based surveys: a recall validation study in Mali among caregivers of febrile children under 5 years

Abstract: BackgroundNationally-representative household surveys are the standard approach to monitor access to and treatment with artemisinin-based combination therapy (ACT) among children under 5 years (U5), however these indicators are dependent on caregivers’ recall of the treatment received.MethodsA prospective case–control study was performed in Mali to validate caregivers’ recall of treatment received by U5s when seeking care for fever from rural and urban public health facilities, community health workers and urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Ashton et al. recently found that caregiver recall surrounding testing and diagnosis to be valid; therefore, the recommendation regarding confirmed malaria cases may need to be reviewed [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ashton et al. recently found that caregiver recall surrounding testing and diagnosis to be valid; therefore, the recommendation regarding confirmed malaria cases may need to be reviewed [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with prior evidence from population-representative household surveys suggesting important gaps in diagnostic testing and ACT taking for children with malaria [ 22 , 25 , 65 ]. While these studies have the advantage of capturing children who are not brought for formal care, household surveys may be subject to recall bias and misunderstanding of clinical actions [ 66 , 67 ]. Our results underscore concerns about insufficient treatment for malaria and highlight the fact that even children who are brought to formal providers often receive inadequate care.…”
Section: Discussionmentioning
confidence: 99%
“…Four types of health facility were included in the study: two urban private facilities, two urban public facilities, two rural public facilities and nine CHWs. Full details of site selection are detailed elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethics approval and consent to participate Approval was obtained from the Ethics Committee of the Malian National Institute for Public Health Research (L'Institut National de Recherche en Santé Publique, INRSP) and from the Tulane University Biomedical Institutional Review Board. Full details of recruitment and consent procedures are available in [27]. Briefly, verbal consent to be contacted for a follow up interview was collected from caregivers at the facility, with full written consent collected during the follow-up visit at their home.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation